Voltage drives diverse endocannabinoid signals to mediate striatal microcircuit-specific plasticity - Mathur, Brian N. (2013)
The dorsolateral striatum and cannabinoid type 1 receptor (CB1) signaling mediate habitual action learning, which is thought to require a balance of activity in the direct and indirect striatal output pathways. However, very little is known about how the high CB1-expressing striatal inhibitory microcircuitry might contribute to long-term plasticity capable of sculpting direct/indirect pathway output. Using optogenetic and molecular interrogation of striatal GABAergic microcircuits, we describe novel mechanisms of voltage-dependent long-term depression of inhibitory synapses (iLTD) onto mouse and rat medium spiny projection neurons (MSNs). This iLTD involves recruitment of different endocannabinoid types and shows both presynaptic and postsynaptic selectivity for MSN subtypes, ultimately resulting in a powerful disinhibition of direct pathway MSNs. These results indicate a new role for voltage states in gating circuit-specific forms of synaptic plasticity and illuminate possible circuit dynamics underlying action control.